Evaluation of Haematological Parameters and Lymphocyte Monocyte Ratio as a Prognostic Marker in Diffuse Large B-cell Lymphoma and T Cell Lymphoma Patients- An Observational Study - Keloth Kavya, Antholi; K Nair, Chandran; Padmanabhan, Maya; Raghavan Sindhu, Edakkadath (Asian Pacific Journal of Cancer Care, 2022)
Background: The present study is a retrospective observational analysis of patients diagnosed with DLBCL and T cell lymphoma during the period of January 2011 to December 2015 at Malabar Cancer Centre, Thalassery. Several studies have shown that ALC and LMR can be used as prognostic indicators for diagnosis, treatment and survival in DLBCL. But there were very few studies done on the correlation of these parameters with T cell lymphoma. So we analysed the influence of haematological parameters in both DLBCL and T cell lymphomas. The primary objective of the present study was to correlate haematological parameters and LMR as predictors of DLBCL and T cell lymphomas. Methods: We analysed total cases of 108 with DLBCL and 25 with T cell lymphomas. The study was done to determine the changes in haematological parameters including WBC count, Platelet count, Hb, HCT, lymphocyte count, monocyte count, ALC, AMC and lymphocyte monocyte ratio in diffuse large B cell lymphoma and T cell lymphomas before and after chemotherapy. Results: The results showed a significant decrease (p˂ 0.05) in the blood platelet counts after chemotherapy in DLBCL. AMC in female patients with DLBCL were decreased (0.69 ± 0.36 to 0.53 ± 0.31; p-value = 0.023) and this was highly significant. LMR was also increased (3.47 ± 3.05 to 5.22 ± 4.34; p-value = 0.048) in female patients with DLBCL. Conclusion: Haematological parameters can be used as a prognostic marker in predicting the extent of disease progression and the effectiveness of the treatment adopted.